Investigation of water quality from the Brahmaputra river in Sherpur district - Islam, MS; Datta, T; Ema, IJ; Kabir, MH; Meghla, NT (Bangladesh Journal of Scientific Research, 2016)
The study was conducted to determine the status of physico-chemical parameters of the Brahmaputra river water in Sherpur district and also to assess the monthly variation of the river water. To perform the study the samples were collected from five different stations during the period of December 2013 to May 2014. Various water quality parameters such as transparency, temperature, electrical conductivity (EC), total dissolved solids (TDS), pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), hardness and alkalinity were examined. The study revealed that a slightly variation in water quality at different stations of the river. The mean value of transparency (42.21 cm), temperature (23.38oC), EC (351.12 ?s/cm), TDS (178.54 mg/l), pH (7.75), DO (4.47 mg/l), BOD (1.02 mg/l), hardness (82.36 mg/l) and alkalinity (98.63 mg/l) showed that the present status of the Brahmaputra river water is suitable for all aquatic lives, domestic and agricultural uses. Although the overall status of the river water quality is suitable, degradation was detected in few points which might be due to anthropogenic activities, especially the direct discharge of domestic effluents into river. Thus, necessary initiatives should be taken against such anthropogenic activities to maintain the overall water quality of the Brahmaputra river for its sustainable use. Bangladesh J. Sci. Res. 28(1): 35-41, June-2015